Rehabilitation of severely resorbed maxilla with a hollow maxillary complete denture - Bhandari, A; Singh, SK; Suwal, P; Parajuli, PK; Manandhar, A (Health Renaissance, 2014)
Rehabilitation of severely resorbed maxilla poses a clinical challenge for fabrication of a successful maxillary complete denture. The increased interridge distance often results in a heavy maxillary complete denture that further reduces the retention and stability of the denture. This case report describes the rehabilitation of an edentulous patient with resorbed maxillary and mandibular ridges and an increased interridge distance by hollow maxillary complete denture so as to reduce the weight of the denture which enhances the retention and stability of the denture. DOI: http://dx.doi.org/10.3126/hren.v11i3.9655 Health Renaissance 2013;11(3):281-283